Leakage Detection In Pipeline Using Wavelength - M.F Ghazali Ghazali; A K Samta (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2019)
Nowadays natural gas transport and distribution is a complex and currently growing and increasing. Natural gas produced from well need to transport in a great distance before reaching it point of use. The pipeline is designed to quickly and efficiently transport the gas from its origin to the high demand area. Either pipelines transportation for water supply or natural gas, leakage is unacceptable problem. Small leak along the pipeline is hard to detect. The objective of this study is to build the test rig galvanized iron and MDPE pipelines. Besides that, the main objective is to determine the leak detection in gas pipeline using wavelet-based filtering. . Main point of each journal is compared in order to determine the problems arise from the previous research. It is then follow by the methodology which will discuss further in this chapter. From methodology, it is known that the data taken can be analysing through Daisy Lab and Math lab software  Wavelet and cross correlation is used to analyse the signal in Matlab. From the result, it show that the leak can be identified based on the peak of amplitude of the signal. The result for galvanized iron pipe is not acceptable due to short pipeline length. Thus it can be concluded that leak can be determined using wavelet-based filtering. As the conclusions, the propose technique can be used to determine the leak in pipelines